2012
DOI: 10.1111/j.1558-5646.2012.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Subfunctionalization of Cyprinid Hypoxia-Inducible Factors for Roles in Development and Oxygen Sensing

Abstract: Gene duplication followed by neo-or subfunctionalization is a major mechanism by which genes with new functions and as-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 56 publications
12
61
0
1
Order By: Relevance
“…Even though one copy retains the ancient hypoxia response, a second copy increases hypoxia-sensitivity. This phenomenon indicates that HIF-α in carp has differentiated functionally during speciation [39]. Furthermore, Chi et al [40] found different evolutionary patterns of HIF-α isoforms in the basal branches of the Actinopterygii and Sarcopterygii.…”
Section: Fish Adaptation Strategies To Long-term Hypoxiamentioning
confidence: 99%
“…Even though one copy retains the ancient hypoxia response, a second copy increases hypoxia-sensitivity. This phenomenon indicates that HIF-α in carp has differentiated functionally during speciation [39]. Furthermore, Chi et al [40] found different evolutionary patterns of HIF-α isoforms in the basal branches of the Actinopterygii and Sarcopterygii.…”
Section: Fish Adaptation Strategies To Long-term Hypoxiamentioning
confidence: 99%
“…The spatiotemporal expression pattern of Hif-3␣1 was also studied in zebrafish and other fishes (55,40,41,25,2). During embryogenesis, Hif-3␣1 mRNA became detectable by RT-PCR as early as 4 h post fertilization (hpf).…”
Section: Spatial and Temporal Expression Of Hif-3a Variantsmentioning
confidence: 99%
“…Therefore, Hif-3␣ might have appeared later in evolution, likely after the emergence of vertebrates. In some teleost fish, the three Hif-3␣ genes may be duplicated due to the teleost specific whole-genome duplication (40).…”
Section: Structure Of Hif-3␣ and Its Variantsmentioning
confidence: 99%
“…TXNRD2, and WNT7B in the ground tit, EPAS1, SIRT7, PLXNA4, and MAFG in the Tibetan mastiff, HIF-1αB in schizothoracine fish could be identified in T. dalaica transcriptome (Supplementary Table S5). In fact, previous study revealed that duplicated HIF alpha paralogs were retained in cyprinids and evolved specialized roles in development and the hypoxic stress response (Rytkonen et al, 2013). In this study, duplicated hif-α (hif-1αA, hif-1αB, hif-2αA, and hif-2αB), EGLN and PPARA were first identified and then used as candidate genes to explore the molecular genetic basis of high altitude adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we chose some known genes involved in high altitude hypoxia to perform further analysis. Duplicated hif-α (hif-1αA, hif-1αB, hif-2αA, and hif-2αB), EGLN1 (1egl 9 homolog 1) and PPARA (peroxisome proliferator-activated receptor-a genes) in cyprinids (Rytkonen et al, 2013;Guan et al, 2014) were downloaded from the National Center for Biotechnology Information (NCBI) and Ensembl version 76 (http://www.ensembl.org/). Each of zebrafish genes was used as query to search against the above corresponding genes obtained from the T. dalaica Swissprot annotations, respectively.…”
Section: Detection Of Natural Selectionmentioning
confidence: 99%